Metabolism of Creative Economy: Its Nexus with Energy Consumption Factors - Utepkaliyeva, Kansulu; Kakizhanova, Tolkyn; Amirova, Ainur; Arzayeva, Maiya; Utaliyeva, Raikhan; Andabayeva, Gulmira (International Journal of Energy Economics and Policy, 2025)
The purpose of this research work is to assess the impact of energy consumption factors on the creative economy. The creative economy is currently associated with green economy, innovation, knowledge, technology and digitalization. It is important to assess whether the creative economy is developing in line with sustainable development goals and with minimal environmental impact. In this context, the authors use the NARDL model to see if energy consumption volume have some impact on creative economy. West Texas Intermediate (WTI or NYMEX) crude oil prices per barrel, Renewable energy consumption (as a percentage of total final energy consumption), Electric net consumption (billion kWh), Refined petroleum product consumption (Mb/d), and Carbon dioxide (CO2) emissions from the power industry (energy) (Mt CO2e) were all considered as independent variables. Total gross value added for creative industries, a dependent variable, was taken on a special request from the National Statistical Bureau. The results of the study show that energy consumption has a clear impact on the creative economy.